A new species of Lycogala, and a new record of Lindbladia from China - Yang, Xin-Ya; Wang, Sai-Yu; Dai, Dan; Zhao, Hui-Nan; Wang, Yang; Li, Xue-Fei; Zhang, Bo; Li, Yu (Phytotaxa, 2023)
Lycogala is one of the most widely known genera of myxomycetes due to its distinct characteristics and cosmopolitan distribution. This study introduces a new species, Lycogala heterospora, based on its morphological characteristics and molecular analyses using the small subunit of the ribosomal RNA (nrSSU) gene. It is characterized by its spores of varying sizes and yellowish-brown peridial vesicles. The characteristics of the new species were examined under a stereomicroscope and a light microscope. The micrographs of relevant details are included. Moreover, Lindbladia cribrarioides is documented for the first time in China.